Research of Dynamic Obstacle Avoidance of Manipulator based on Artificial Potential Field Method of Velocity Field - Shi Yafei; Zhang Li; Liu Zixuan; Lü Yiping (Jixie chuandong)
In order to improve the safety and accuracy of the manipulator in dynamic obstacle avoidance，an artificial potential field collision avoidance algorithm based on velocity field is proposed.Firstly，the attracted velocity field is established to obtain the trajectory of the manipulator tracking the moving target.Then，the repulsive velocity field is constructed by combining the danger field method，so that the manipulator can realize dynamic obstacle avoidance and safety assessment in the multi-obstacle environment.Finally，aiming at the problem that the artificial potential field method is easy to fall into the local minimum，the method of adding additional velocity in the normal direction of sum velocity is proposed to escape the local minimum value.The algorithm is validated by using Matlab Robotics Tool.The results show that the artificial potential field method based on velocity field can realize dynamic target tracking，move obstacle avoidance and safety evaluation of the manipulator.